Let it begin here! : April 19, 1775 : the day the American Revolution began - Brown, Don, 1949- (Flash Point/Roaring Brook Press, 2008)
Provides an informative look at the events that lead up to this important day in history when American heroes took a stand against an oppressive monarch in order gain the freedom they deserved in the new land they worked hard to build.